2018
DOI: 10.1021/acs.jpclett.7b03310
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Role of an Aqueous Environment on the Electronic Structure and Ionization of Phenol Using Photoelectron Spectroscopy

Abstract: Water is the predominant medium for chemistry and biology, yet its role in determining how molecules respond to ultraviolet light is not well understood at the molecular level. Here, we combine gas-phase and liquid-microjet photoelectron spectroscopy to investigate how an aqueous environment influences the electronic structure and relaxation dynamics of phenol, a ubiquitous motif in many biologically relevant chromophores. The vertical ionization energies of electronically excited states are important quantiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…ps* state mediated O-H bond fission in the isolated molecule has been extensively studied, both experimentally and theoretically, [5,6,8,10,11,[45][46][47] and recent ultrafast time-resolved studies following near-UV excitation of phenol in aqueous solution have revealed spectral signatures of both phenoxyl radicals and solvated electrons. [48,49] Such findings accord with the earlier theoretical predictions by Domcke and Sobolewski, who showed that the ps* state of phenol is stabilized when bound to a small cluster of water molecules. [45] In contrast to the isolated phenol molecule, the ps* state of the phenol-water cluster is formed by promoting an electron from a phenol-centred p-orbital to a s*-orbital centred on an O-H bond of a complexing H2O molecule.…”
Section: Introductionsupporting
confidence: 90%
“…ps* state mediated O-H bond fission in the isolated molecule has been extensively studied, both experimentally and theoretically, [5,6,8,10,11,[45][46][47] and recent ultrafast time-resolved studies following near-UV excitation of phenol in aqueous solution have revealed spectral signatures of both phenoxyl radicals and solvated electrons. [48,49] Such findings accord with the earlier theoretical predictions by Domcke and Sobolewski, who showed that the ps* state of phenol is stabilized when bound to a small cluster of water molecules. [45] In contrast to the isolated phenol molecule, the ps* state of the phenol-water cluster is formed by promoting an electron from a phenol-centred p-orbital to a s*-orbital centred on an O-H bond of a complexing H2O molecule.…”
Section: Introductionsupporting
confidence: 90%
“…Fig. 1a shows the absorption spectra computed with phenol solvated by a different number of water molecules, as well as the experimental spectrum 35 in gas phase and in aqueous solution. In order to evaluate the solvatochromic effects, also the computed gas-phase spectrum is included.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental spectrum in aqueous solution has a maximum at 4.59 eV 35,86 while the one in the gas phase possesses few vibronic transitions 35,85 around 4.6 eV (270 mm), indicating that the solvent barely affects the energy-range of the spectra. The calculated spectra show small shifts, depending on the model used, which are within the error of the method.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of experimental techniques have been developed by the scientists to explore the photodissociation of phenol, such as H Rydberg atom photofragment translational spectroscopy, velocity map ion imaging, high‐resolution time‐of‐flight spectra and multimass ion imaging . Ratzer et al measured the lifetimes of excited states, and observed the increased OH bond, the shortened CO bond and the expanded aromatic ring on electronic excitation.…”
Section: Introductionmentioning
confidence: 99%